2019
DOI: 10.1038/s41598-019-46563-4
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum depression and infant care, sleep and growth

Abstract: Peripartum depression is a common, serious complication in mothers. To assess the influence of infant care, sleep and growth on the risk of peripartum depression, 1,271 mothers of healthy one-month-old infants completed comprehensive questionnaires including the Edinburgh Postnatal Depression Scale. Relationships between high depression scores and variables related to infants’ care, sleep and growth were assessed adjusting for other variables. High depression scores were found in 233 mothers, which were associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Interventions addressing socioeconomic hardships may be critical in addressing disparities in adolescent birth outcomes. Additionally, pregnant adolescents are at high risk of mental health disorders (Siegel & Brandon, 2014 ), and peripartum mood disorders are associated with poorer birth outcomes and growth (Iwata et al, 2019 ; Traviss et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions addressing socioeconomic hardships may be critical in addressing disparities in adolescent birth outcomes. Additionally, pregnant adolescents are at high risk of mental health disorders (Siegel & Brandon, 2014 ), and peripartum mood disorders are associated with poorer birth outcomes and growth (Iwata et al, 2019 ; Traviss et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies need to address the potential benefit of relatively clearer lighting cycles for newborn infants to promote the early establishment of night timedominant sleep patterns. Given that the night time sleep duration of infants is one of primary independent variables of their mothers' sleep 41 and that insufficient sleep duration of the mothers is an established independent variable of peripartum depression, 42 the improvement in the light cycle may help accelerate the acquisition of a matured sleep cycle, and help prevent peripartum depression and subsequent suicides and child neglect.…”
Section: S12mentioning
confidence: 99%
“…In contrast, for mothers, unfamiliar child-rearing fatigue is likely to occur one month after giving birth, which makes the development of maternity blues and postpartum depression more likely 5 . Previous studies have reported that sleep time in children and sleep satisfaction in mothers affect postpartum depression 6 . In addition, since the mother’s sleep in the early stages after childbirth is strongly influenced by the sleep schedule of the child 7 , 8 , early establishment of a sleep–wake rhythm for the child may reduce the risk of mental health problems for the mother.…”
Section: Introductionmentioning
confidence: 97%